PENGARUH PENERAPAN METODE TERAPI KOMUNIKASI TOTAL TERHADAP PASIEN AFASIA GLOBAL PASCA STROKE: Effect of Application of Total Communication Therapy Method on Post-Stroke Global Aphasia Clients - Hendra Djuhendi; Popon Popon (JURNAL TERAS KESEHATAN, 2021)
Background: Individuals with aphasia experience speech, listening and writing disorders although they do not affect intelligence due to brain damage which contains language, usually on the left side of the left cerebral hemisphere. Aphasia cases can be handled by semantic divergent methods. Objective: This study aims to determine the treatment of adult aphasia patients who have impaired word discovery, compose sentences that sometimes express them not using the correct sentence structure, using the semantic divergent method. There were also some patients who experienced disturbances in the relationship between thought processes and language; the inability to turn thoughts into sentences. This study was conducted on a female patient with Global Aphasia Post Stroke aged 84 years at the Cibabat Regional General Hospital, Cimahi. Methods: The research method used is experimental case study research which aims to determine the condition of the subject before and after intervention or therapy. Data collection was carried out through the WOTS stage, namely interviews with the client's parents, direct observation of clients, conducting tests on clients, and study of patient medical record documents. Conclusion: The results showed that after 20 sessions of therapy, the ability to designate the patient's noun level increased where the initial test scored 0 points and the final test scored 8 points with a success percentage of 80% of the maximum 10 points get tested. Based on these results it can be concluded that the application of total communication methods in global aphasia patients is successful.